Improved charge extraction in inverted perovskite solar cells with dual-site-binding ligands - Chen, Hao; Liu, Cheng; Xu, Jian; Maxwell, Aidan; Zhou, Wei; Yang, Yi; Zhou, Qilin; Bati, Abdulaziz S R; Wan, Haoyue; Wang, Zaiwei; Zeng, Lewei; Wang, Junke; et al. (Science (American Association for the Advancement of Science), 2024)
Inverted (pin) perovskite solar cells (PSCs) afford improved operating stability in comparison to their nip counterparts but have lagged in power conversion efficiency (PCE). The energetic losses responsible for this PCE deficit in pin PSCs occur primarily at the interfaces between the perovskite and the charge-transport layers. Additive and surface treatments that use passivating ligands usually bind to a single active binding site: This dense packing of electrically resistive passivants perpendicular to the surface may limit the fill factor in pin PSCs. We identified ligands that bind two neighboring lead(II) ion (Pb ) defect sites in a planar ligand orientation on the perovskite. We fabricated pin PSCs and report a certified quasi-steady state PCE of 26.15 and 24.74% for 0.05- and 1.04-square centimeter illuminated areas, respectively. The devices retain 95% of their initial PCE after 1200 hours of continuous 1 sun maximum power point operation at 65°C.